1988
DOI: 10.1007/bf01650508
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial treatment of otitis and sinusitis with ciprofloxacin and penicillin V — A comparison

Abstract: 80 adult outpatients suffering from otitis media, sinusitis (maxillaris or frontalis) or peritonsillitis were treated with 500 mg ciprofloxacin b.i.d. (n = 40) or with 2 g penicillin V t.i.d. (n = 40). The patients were randomly allocated. Three groups of patients resulted, clinically and bacteriologically evaluable, or only clinically evaluable because the isolated strains were resistant to ciprofloxacin or penicillin V or because no strains were isolated. Ciprofloxacin was superior to penicillin V; there wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…5,6 Gentamicin ototoxicity and nephrotoxicity are well known. 9,10 Reduced bactericidal effect against Pseudomonas and Enterobacteriaceae has also been observed. 9,10 Reduced bactericidal effect against Pseudomonas and Enterobacteriaceae has also been observed.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…5,6 Gentamicin ototoxicity and nephrotoxicity are well known. 9,10 Reduced bactericidal effect against Pseudomonas and Enterobacteriaceae has also been observed. 9,10 Reduced bactericidal effect against Pseudomonas and Enterobacteriaceae has also been observed.…”
Section: Introductionmentioning
confidence: 94%
“…It acts as an inhibitor of bacterial topoisomerase II (DNA gyrase) and its homologue topoisomerase IV, enzymes that are required for bacterial DNA replication, and has in vitro activity against a wide range of Gram-negative and Gram-positive bacteria. [8][9][10][11][12][13][14] However, the need to administer high doses to achieve acceptable tissue concentrations, with the consequent possibility of side effects and high costs, have led investigators to the idea of applying ciprofloxacin to the ear topically. Different trials have shown that ciprofloxacin, unlike aminoglycosides, does not show ototoxicity at the cochleovestibular level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most were ineligible for our meta-analysis: 48 did not use the reference drugs pertinent to this analysis, three inextricably combined patients with sinusitis with those with other infections,911 and two inextricably combined patients with acute, chronic, and recurrent sinusitis. 12 13 Of the 27 trials that qualified for our meta-analysis, six were placebo controlled (one study comparing amoxycillin also had a placebo arm),14 – 19 13 compared amoxycillin with other antibiotics, 16 20 – 31 and eight compared a folate inhibitor (co-trimoxazole, trimethoprim plus sulfametopyrazine, or brodimoprim) with other antibiotics 32 – 39.…”
Section: Trial Characteristics and Quality Assessmentmentioning
confidence: 99%
“…In addition to complicated urinary tract infections [5], gastrointestinal infections [6], gonorrhea [7], cipro oxacin was widely used in the therapy of lower respiratory tract infections [8], skin and soft tissue infections [9], sinusitis [10], otitis media [11], sepsis [12], etc. Cipro oxacin exhibits excellent antimicrobial activity against many pathogens, such as some Gram-positive organisms including staphylococci, streptococci, and most of Gram-negative organisms consisting of Hemophilus in uenzae, Escherichia coli, Enterobacter, P. aeruginosa species.…”
Section: Introductionmentioning
confidence: 99%